Physician factors affecting patient preferences in selecting a primary care provider: A qualitative research study in Singapore. - Abigail Ern Jie Lee; Sulaiha Ithinin; Ngiap Chuan Tan (PLoS ONE)
Background Care continuity by a dedicated, well-trained primary care physician (PCP) has shown to improve health outcomes of patients with non-communicable diseases (NCDs). In Singapore's fee-for-service primary care system, patients can choose to consult any PCP in either a public (polyclinic), private (General Practitioners/ GP), or both types of clinics, resulting in potential fragmented care. Decision-making by patients in selecting their preferred PCP remains unclear. This study aims to explore the personal factors influencing the choice of PCP among patients with NCDs in primary care. Methods This qualitative research study was conducted in a typical polyclinic. In-depth interviews were conducted on patients with NCDs. Purposive sampling was implemented to enrol patients who had previously consulted PCPs in polyclinics and GP clinics, garnering their perspectives and experiences of care received from both providers. Interviews were audio-recorded, transcribed, and audited. Data was coded and analysed using thematic content analysis to identify emerging themes. The physician-specific factors which influence patients' decision-making of PCP selection are presented here. Results Twenty-one Asian patients aged 38 to 82 years were interviewed. They preferred PCPs with an approachable and genuine demeanour, exhibiting empathy and compassion. They valued the PCPs' verbal, non-verbal and listening skills. Regarding professional qualities, patients wanted PCPs to demonstrate competency and a patient-centred care approach. Some selected their PCP based on compatible age and gender that they felt comfortable with. Establishing good rapport with their PCP and maintaining continuity of care were deemed as major factors in patients' PCP selection. Conclusion Patients tended to select PCPs based on their personal characteristics, interpersonal skills, professional attributes, demographics, and the physician-patient relationship. PCPs should be aware of these attributes and demonstrate them during their patient interaction. Leveraging on this enables PCPs to build rapport with their patients and maintain care continuity to optimize their health outcomes.